NDPS Act and Juvenile Justice System: A Critical Analysis of Juvenile Drug Inhalation in India (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Legislators, judges, and social organizations in India are very worried about the disturbing increase in juvenile drug inhalation. Understudied but crucial among the many elements impacting young people's behavioural and criminal trajectories is narcotic drug usage. The purpose of this research is to examine if there is a connection between drug use and the emergence of antisocial behaviour in Indian youth. This study delves at the complex web of factors psychological, social, economic, and familial that put teenagers at risk for substance abuse and criminal activity. It takes an interdisciplinary approach by drawing on the fields of law, psychology, and criminology. In addition to examining the links between drug misuse and juvenile delinquency, the study also assesses legislative frameworks such the Child Welfare and Juvenile Justice Act of 2015 and the Narcotic Substances and Care Act of 1985. The results highlight the need for holistic intervention plans that address narcotic-induced delinquency by integrating mental health services, community assistance, and education. By providing practical recommendations for reforming Indian law, public policy, and adolescent rehabilitation programs, this study adds to the larger conversation on juvenile justice.